Understanding the Kitab al-Kāfī by Abū Ja'far al-Kulainī: A Study of the Prophet's Will to 'Alī ibn Abī Ṭālib in Rauḍat al-Kāfī - Jubaedah, Siti; Millah, Mus'idul; Burhani, Nasih (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2024)
AbstractThis article discusses al-Ka>fi>, written by Abu Ja'far Al-Kulaini>, with an emphasis on studying the Prophet Muhammad’s will to ‘Ali>> ibn Abī Ṭālib found in the section Raudat al-Ka>fi>. As the third part of al-Ka>fi>, Raudat al-Ka>fi> consists of a collection of hadiths that cover various religious aspects, including the letters and sermons of the Imam, which have a different system compared to the previous two sections. This article highlights the importance of the Prophet's will in the context of leadership and the spiritual authority of ‘Ali>> by discussing key themes contained in the will, namely justice, wisdom, and social responsibility. This article offers a perspective on the influence of these teachings within the Shia hadith and their relevance in contemporary society. This analysis is expected to deepen understanding of al-Ka>fi>’s contribution to the development of Islamic thought and the significance of the relationship between the Prophet and ‘Ali>> in Islamic history.Keywords: al-Ka>fi>, Raud}at al-Ka>fi>, Will. AbstrakArtikel ini membahas kitab Al-Kāfī yang ditulis oleh Abū Ja‘far al-Kulainī, dengan penekanan pada studi wasiat Nabi Muhammad kepada ‘Alī ibn Abī Ṭālib yang terdapat dalam bagian Rauḍat al-Kāfī. Sebagai bagian ketiga dari Al-Kāfī, Rauḍat al-Kāfī terdiri dari kumpulan hadis yang mencakup berbagai aspek keagamaan, termasuk surat dan khutbah Imam, yang memiliki sistematika berbeda dibandingkan dua bagian sebelumnya. Artikel ini menyoroti pentingnya wasiat Nabi dalam konteks kepemimpinan dan otoritas spiritual ‘Ali>>. Dengan membahas tema-tema kunci yang terkandung dalam wasiat, seperti keadilan, kebijaksanaan, dan tanggung jawab sosial, artikel ini menawarkan perspektif tentang pengaruh ajaran tersebut dalam tradisi Syiah dan relevansinya dalam masyarakat kontemporer. Analisis ini diharapkan dapat memperdalam pemahaman tentang kontribusi Al-Kāfī terhadap pengembangan pemikiran Islam dan signifikansi hubungan Nabi dan ‘Ali>> dalam sejarah Islam. Kata Kunci: al-Ka>fi>; Raud}at al-Ka>fi; Wasiat.